The effect of COVID-19 and sex differences on natural killer cell cytotoxicity - Dagar, Arushi; Polyak, Maria J.; Mok, Adley C. H.; Feehan, David; Potemkin, Michael; Tremblay, Alain; Mody, Christopher H. (Frontiers in Cellular and Infection Microbiology, 2025)
COVID-19 has caused more than 7 million deaths worldwide, and according to the World Health Organization, it continues to result in more than 1000 reported deaths per month at the time of this writing. It is crucial to understand the immune response to COVID-19 since the virus continues to persist. Natural killer (NK) cells play a critical role in the immune defense against viral infections, including COVID-19. While it is well documented that infected patients have a reduction in lymphocytes and NK cells, gaps in knowledge exist regarding the function of NK cells. To study the function of NK cells in patients hospitalized with COVID-19, peripheral blood was obtained from patients admitted to the medical (non-ICU) wards at a large tertiary hospital. We demonstrated a decrease in the mature cytotoxic subset of NK cells within the peripheral blood of patients hospitalized with COVID-19. We also observed a notable reduction in the cytotoxic function of NK cells against tumor targets. We examined the mechanisms leading to NK cell killing. We found reductions in the intracellular levels of effector molecules, the degranulation of cytotoxic granules, and the extracellular concentrations of released effector molecules. We identified dysfunctional intracellular granule trafficking required to position the granules for degranulation, which would be consistent with the reduced release of effector molecules. We found clusters of inhibitory receptors were upregulated in subsets of NK cells, in keeping with inhibition of cytotoxicity. Additionally, males with COVID-19 showed NK cell defects compared to healthy males, while no significant differences were observed in females. Our findings highlight defects in cytolytic effector molecules, granule trafficking and release, and increased expression of inhibitory receptors on NK cells in patients hospitalized with COVID-19, in addition to a sex difference in cytolytic function, which contributes to defective NK cell function in COVID-19.